Measurements of Aerosol Size and Microphysical Properties: A Comparison Between Raman Lidar and Airborne Sensors. Issue 14 (19th July 2022) - Di Girolamo, P.; De Rosa, B.; Summa, D.; Franco, N.; Veselovskii, I.
Abstract: This manuscript compares measurements of aerosol size distributions and microphysical properties retrieved from the Raman lidar BASIL with those obtained from a series of aircraft sensors during HyMeX‐SOP1. The attention is focused on a measurement session on 02 October 2012, with BASIL measurements revealing the presence of a lower aerosol layer extending up to 3.3 km and an elevated layer extending from 3.6 to 4.6 km. Aerosol size distribution and microphysical properties are determined from multi‐wavelength particle backscattering and extinction profile measurements through a retrieval approach based on Tikhonov regularization. A good agreement is found between BASIL and the microphysical sensors' measurements for all considered aerosol size and microphysical properties. Specifically, BASIL and in‐situ volume concentration values are in the range 2–5 μm 3 cm −3 in the lower layer and in the range 1–3.5 μm 3 cm −3 in the upper layer. Values of the effective radius values from BASIL and the in‐situ sensors are in the range 0.2–0.6 μm in both the lower and upper layer. Aerosol size distributions are determined at 2.2, 2.8, 4 and 4.3 km, with a good agreement between the Raman lidar and the microphysical sensors at all considered heights. We combined these size and microphysical results with Lagrangian back‐trajectory analyses and chemical composition measurements. From this combination of datasets we conclude that aerosol particles below 3 km were probably originated by wildfires in North America and/or by anthropogenic activities in North‐Eastern Europe, while aerosols above 3 km were also probably originated by wildfires in North America. Plain Language Summary: Physical and chemical properties of aerosol particles obtained from a multi‐wavelength Raman lidar and airborne in‐situ microphysical and chemical sensors. A retrieval scheme exploiting Tikhonov's inversion is applied to the lidar measurements to infer aerosol size and microphysical properties. A good agreement between the lidar and the in‐situ sensors is found for all considered parameters. Ensemble back‐trajectory modeling and measurements are combined to determine the types and origin of the aerosol particles and source‐receptor relationships. Key Points: Aerosol physical and chemical characteristics from a three‐wavelength Raman lidar and airborne microphysical and chemical sensors A retrieval approach based on Tikhonov regularization is applied to lidar measurements to infer aerosol size and microphysical properties Ensemble back‐trajectory modeling and measurements combined to determine aerosol types and origins and their source–receptor relationships